Association of Kidney Tissue Barrier Disrupture and Renal Dysfunction in Resuscitated Murine Septic Shock. Issue 4 (October 2016) - Stenzel, Tatjana; Weidgang, Clair; Wagner, Katja; Wagner, Florian; Gröger, Michael; Weber, Sandra; Stahl, Bettina; Wachter, Ulrich; Vogt, Josef; Calzia, Enrico; Denk, Stephanie; Georgieff, Michael; et al.
Abstract : Abstract: Septic shock-related kidney failure is characterized by almost normal morphological appearance upon pathological examination. Endothelial barrier disrupture has been suggested to be of crucial importance for septic shock-induced organ dysfunction. Therefore, in murine resuscitated cecal ligation and puncture (CLP)-induced septic shock, we tested the hypothesis whether there is a direct relationship between the kidney endothelial barrier injury and renal dysfunction. Anesthetized mice underwent CLP, and 15 h later, were anesthetized again and surgically instrumented for a 5-h period of intensive care comprising lung-protective mechanical ventilation, fluid resuscitation, continuous i.v. norepinephrine to maintain target hemodynamics, and measurement of creatinine clearance (CrCl). Animals were stratified according to low or high CrCl. Nitrotyrosine formation, expression of the inducible isoform of the nitric oxide synthase, and blood cytokine (tumor necrosis factor, interleukin-6, interleukin-10) and chemokine (monocyte chemoattractant protein-1, keratinocyte-derived chemokine) levels were significantly higher in animals with low CrCl. When plotted against CrCl and neutrophil gelatinase-associated lipocalin levels, extravascular albumin accumulation, and tissue expression of the vascular endothelial growth factor and angiopoietin-1 showed significant mathematical relationships related to kidney (dys)function. Preservation of the constitutive expression of the hydrogen sulfide producing enzyme cystathione-γ-lyase was associated with maintenance of organ function. The direct quantitative relation between microvascular leakage and kidney (dys)function may provide a missing link between near-normal tissue morphology and septic shock-related renal failure, thus further highlighting the important role of vascular integrity in septic shock-related renal failure.